Practical Handbook for International Students, 2013 - (:unkn) unknown (My University, 2013)
Practical Handbook for International Students, 2013 Prepared for publication in 2013 by International Relations Department, Public Relations Department, University of Latvia Press.
Keywords: Exploring Latvia; Studying; Living in Latvia; University of Latvia